2016
DOI: 10.1074/jbc.m116.718999
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B Activity Initiates Apoptosis via Digestive Protease Activation in Pancreatic Acinar Cells and Experimental Pancreatitis

Abstract: Pancreatitis is associated with premature activation of digestive proteases in the pancreas. The lysosomal hydrolase cathepsin B (CTSB) is a known activator of trypsinogen, and its deletion reduces disease severity in experimental pancreatitis. Here we studied the activation mechanism and subcellular compartment in which CTSB regulates protease activation and cellular injury. Cholecystokinin (CCK) increased the activity of CTSB, cathepsin L, trypsin, chymotrypsin, and caspase 3 in vivo and in vitro and induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(95 citation statements)
references
References 56 publications
(77 reference statements)
3
89
0
Order By: Relevance
“…Pancreatitis starts with a premature activation of digestive enzymes within pancreatic acinar cells, resulting in cell injury. 4,5 This process is paralleled by an infiltration of inflammatory cells, 6,7 and macrophages and neutrophils are the first to reach the organ and contribute to pancreatic damage. [6][7][8][9] Macrophages, the dominant leukocyte population infiltrating the pancreas during severe acute pancreatitis (SAP), have been found to differentiate into a pro-inflammatory M1-phenotype while phagocytosing areas of necrotic tissue.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Pancreatitis starts with a premature activation of digestive enzymes within pancreatic acinar cells, resulting in cell injury. 4,5 This process is paralleled by an infiltration of inflammatory cells, 6,7 and macrophages and neutrophils are the first to reach the organ and contribute to pancreatic damage. [6][7][8][9] Macrophages, the dominant leukocyte population infiltrating the pancreas during severe acute pancreatitis (SAP), have been found to differentiate into a pro-inflammatory M1-phenotype while phagocytosing areas of necrotic tissue.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Previous studies have confirmed that the pathogenesis of AP caused by cerulein involved apoptosis and autophagy [4,5,6,7]. Therefore, we are to present that PSS exerts its pharmacological activities through the MEK/ERK pathway in relation to apoptosis and autophagy.…”
Section: Introductionmentioning
confidence: 87%
“…26 Isolated acini were cultured in RPMI-1640 medium containing penicillin (50 U/mL) and streptomycin (50 μg/mL) supplemented with 10% serum at 37°C in a 5% CO 2 atmosphere. The pancreas of three mice were pooled to get enough cells for the experimental setting.…”
Section: Cells Isolationmentioning
confidence: 99%